2013
DOI: 10.1073/pnas.1310755111
|View full text |Cite
|
Sign up to set email alerts
|

Pch2 is a hexameric ring ATPase that remodels the chromosome axis protein Hop1

Abstract: In budding yeast the pachytene checkpoint 2 (Pch2) protein regulates meiotic chromosome axis structure by maintaining the domain-like organization of the synaptonemal complex proteins homolog pairing 1 (Hop1) and molecular zipper 1 (Zip1). Pch2 has also been shown to modulate meiotic double-strand break repair outcomes to favor recombination between homologs, play an important role in the progression of meiotic recombination, and maintain ribosomal DNA stability. Pch2 homologs are present in fruit flies, worms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(116 citation statements)
references
References 69 publications
8
107
1
Order By: Relevance
“…This finding supports the idea that when these proteins are aberrantly expressed in cells that lack the proteins necessary to subsequently remove them (e.g., Chen et al 2014;Lambing et al 2015), they may make chromosomes "sticky," driving aberrant interactions and missegregation. Recently, we found that a unique allele of ASY1, the A. thaliana homolog of HORMAD1/ HORMAD2 and Hop1 (Armstrong et al 2002), underwent a dramatic selective sweep following WGD in A. arenosa (Hollister et al 2012;Yant et al 2013).…”
Section: Dmc1supporting
confidence: 79%
“…This finding supports the idea that when these proteins are aberrantly expressed in cells that lack the proteins necessary to subsequently remove them (e.g., Chen et al 2014;Lambing et al 2015), they may make chromosomes "sticky," driving aberrant interactions and missegregation. Recently, we found that a unique allele of ASY1, the A. thaliana homolog of HORMAD1/ HORMAD2 and Hop1 (Armstrong et al 2002), underwent a dramatic selective sweep following WGD in A. arenosa (Hollister et al 2012;Yant et al 2013).…”
Section: Dmc1supporting
confidence: 79%
“…In some instances, an AAA-ATPase can bind to different adaptor proteins, thus changing its substrate specificities and cellular functions (19). In the case of the TRIP13 AAA-ATPase and of its homologs, a role in meiotic recombination has been reported in mice, yeast, worms, and plants (25)(26)(27)(28). This function has been explained by their action to dislocate certain proteins from Recombinant Cdc20-Mad2 complex was expressed and purified as described in Materials and Methods and was added to the assay at 2 nM.…”
Section: Discussionmentioning
confidence: 99%
“…2A. chromatin (26)(27)(28). A different function of TRIP13 has been suggested by a proteomic data mining study that identified it as a kinetochore protein that interacts with p31 comet (16).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the Walker A motif are known to disrupt ATP binding, whereas Walker B motif mutations disrupt ATP hydrolysis (2). Both were shown to be essential for the function of TRIP13 in yeast (13). The present study generated TRIP13 mutants that have mutations either in the Walker A or Walker B motifs, or in both motifs, including TRIP13-GK/AA, which has glycine 184 and lysine 185 in the Walker A motif substituted with alanine; and TRIP13-DE/NQ, which has aspartic acid 252 and glutamic acid 253 in the Walker B motif substituted with asparagine and glutamine, respectively; and TRIP13-GK/AA-DE/NQ, which has both mutations.…”
Section: Hct116 Cells That Constitutively Expressed Either Flag Ormentioning
confidence: 99%
“…Accumulating studies have demonstrated that TRIP13 plays pivotal roles in meiotic recombination and DNA repair in plants, yeast, worms and mice (8)(9)(10)(11)(12). TRIP13 forms a stable hexameric ring, and ATP binding, as well as ATP hydrolysis, are critical for the function of the protein (13). Previous studies have revealed that TRIP13 is a novel component of the spindle assembly checkpoint (SAC) pathway (14)(15)(16)(17), which is crucial for the accurate distribution of duplicated chromosomes (18).…”
Section: Introductionmentioning
confidence: 99%